2007
DOI: 10.1111/j.1440-1681.2007.04819.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection by and Anti‐oxidant Mechanism of Berberine Against Rat Liver Fibrosis Induced by Multiple Hepatotoxic Factors

Abstract: 1. The aim of the present study was to investigate the effect and mechanism of berberine, an alkaloid extracted from the traditional Chinese medicine coptis, on rat liver fibrosis induced by multiple hepatotoxic factors. 2. Male Wistar rats were separated into five groups, a normal control group, a fibrotic control group and fibrotic groups treated with three different doses of berberine. The fibrotic models were established by introduction of multiple hepatotoxic factors, including CCl(4), ethanol and high ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects. [4][5][6][7] Our previous studies found that BBR could reinforce the intestinal epithelial tight junction and reduce epithelial intestinal permeability in vitro and in vivo, which is important to maintain the intestinal mucosal barrier function. [8][9][10] Therefore, in order to further explore the protective effect of BBR on the intestinal mucosal barrier damage induced by peritoneal air exposure, it is important to determinate the changes in the intestinal mucosa barrier function during peritoneal air exposure under experimental conditions mimicking clinical operation room atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Many studies have shown that BBR exhibits multiple pharmacological activities including antioxidant, anti-microbial, anti-tumor, and cholesterol-lowering effects. [4][5][6][7] Our previous studies found that BBR could reinforce the intestinal epithelial tight junction and reduce epithelial intestinal permeability in vitro and in vivo, which is important to maintain the intestinal mucosal barrier function. [8][9][10] Therefore, in order to further explore the protective effect of BBR on the intestinal mucosal barrier damage induced by peritoneal air exposure, it is important to determinate the changes in the intestinal mucosa barrier function during peritoneal air exposure under experimental conditions mimicking clinical operation room atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Its chemical structure is 5,8-dihydro-9,10-dimethoxy-6H-benzo(g)-1,3-benzodioxolo(5,6-a)quinolizine. Berberine exhibits a wide variety of bioactivities such as antidiarrheic (Sack and Froehlich, 1982;Taylor and Greenough, 1989), antimicrobial (Yan et al, 2008), hypolipidemic (Kong et al, 2004;Doggrell, 2005;Brusq et al, 2006;Cicero et al, 2007), hypoglycemic (Yin et al, 2002;Pan et al, 2003;Zhou et al, 2007;Turner et al, 2008;Yin et al, 2008), antiarrhythmic (Wang et al, 1994;Lau et al, 2001), anticancer (Inoue et al, 2005;Lanvers-Kaminsky et al, 2006;Lin et al, 2006Lin et al, , 2007Piyanuch et al, 2007;Serafim et al, 2008;Yu et al, 2007), anti-inflammatory (Kuo et al, 2004Lee et al, 2007), antiviral (Hayashi et al, 2007), antidepressant (Kulkarni and Dhir, 2007), and hepatoprotective (Zhang et al, 2008) effects. Its chloride salt has been used for several decades in clinical situations to treat gastroenteritis and secretory diarrhea in China.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have clearly demonstrated that berberine exerted anti-fibrotic effects possibly through activation of AMP-activated protein kinase, blocking NADPH oxidase 4 and Akt expression and reduction in the expression of α-SMA [51]. The effect of berberine on rat liver fibrosis induced by multiple hepatotoxic factors, including CCl 4 , ethanol, and high cholesterol, demonstrated that berberine could prevent experimental liver fibrosis by regulating the anti-oxidant system and lipid peroxidation [52] .…”
Section: Berberinementioning
confidence: 99%
“…Moreover, berberine dramatically decreased the number of activated HSCs, the amount of fibrotic septa, and the content of hepatic collagen prevents CCl 4 induced experimental liver fibrosis. Berberine treatment also caused the decrease in the secreation of TGF-β1 and inhibits HSC activation [52] . Further clinical investigations would be necessary to determine whether berberine could be effective for the prevention of liver fibrosis in humans.…”
Section: Berberinementioning
confidence: 99%